Improving sound insulation in low frequencies by multiple band-gaps in plate-type acoustic metamaterials. (November 2020) - Zhou, Xiaoling; Wang, Longqi; Qin, Li; Peng, Fujun
Abstract: According to the mass law, low-frequency sound attenuation is very difficult in engineering because the mass and space of structures are usually limited. In this paper, we propose a plate-type acoustic metamaterial with good sound insulation in low-frequency ranges. By attaching multilayered rubber and metal cylinders on a thin plate, multiple flexural wave band-gaps at low-frequency ranges are obtained. The band structures and eigenmodes are elucidated by finite element calculations. Both the flexural wave transmission spectra and the sound transmission loss are investigated. The results show that the obtained multiple band-gaps lead to more than one sound insulation peak at low frequencies. The geometrical parameter effects on the band-gap frequencies are discussed. By combining cells with different geometrical parameters, the formed supercell can improve the low-frequency sound insulation efficiency and introduce much more variety. The results in this paper will be useful for sound and vibration control in engineering applications. Highlights: Plate-type acoustic metamaterial with multiple resonators are investigated. Multiple flexural band gaps appear at low frequency. The multiple band-gaps lead to large sound insulation peaks. Sound transmission loss can be improved by designing the cell geometrical parameters.